Prognostic significance of pretreatment 18F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) in patients with primary T cell lymphomas. Issue 2 (15th November 2021) - Zhang, Jian-Hua; Zhao, Jing; Fan, Yan; Fu, Zhan-Li; Zhang, Xu-Chu; Liu, Meng; Zhao, Guang-Yu; Cen, Xi-Nan; Chen, Xue-Qi; Ning, Jing; Li, Xiang; Wang, Rong-Fu
Abstract : Objective: T cell lymphomas are associated with an aggressive worse prognosis. This study is designed to assess T cell lymphomas using 18 F-FDG PET/CT. Methods: Sixty-four patients with newly diagnosed T cell lymphomas underwent PET/computed tomography (PET/CT) scans, 47 cases who were fully followed up were retrospectively reviewed and analyzed. Overall survival (OS) and progression-free survival (PFS) were recorded for prognosis. We measured the maximum standardized uptake value (SUVmax ) in all cases, analyzed the correlation between SUVmax and survival and other clinicopathologic parameters. Kaplan–Meier log-rank tests were then used to compare the survival of high and low PET/CT parameter groups, and multivariate Cox proportional hazards regression analysis was carried out to identify predictors of OS and PFS. Results: With a median follow-up of 26.5 (range 0.7–117.5) months, the 1-, 2- and 3-year OS were 75.6, 61.7 and 49.2%, and PFS were 49.3, 39.9 and 29.9%, respectively in 47 patients. Among them, 33 cases progressed with a median time of 9.5 (0.7–115.0) months, and 26 patients died with a median survival time of 26.5 (0.7–117.5) months. Multivariate analysis showed the following independent prognostic factors for OS: age >60 years ( P  = 0.002), SUVmax >9.7 ( P  = 0.009) and extranodal involvement of more than one site ( P  = 0.018). In addition, lactate dehydrogenase level ( P  = 0.003) and B symptoms ( P  = 0.018) were independent risk factors for PFS. Conclusion: Pretherapy SUVmax may serve as an independent predictor of outcome in patients with newly diagnosed T cell lymphomas.